Informal Alliance - Gijswijt, Thomas W., author.
1 online resource (322 pages)
Keywords: Informal Alliance is the first archive-based history of the secretive Bilderberg Group, the high-level transatlantic elite network founded at the height of the Cold War. Making extensive use of the recently opened Bilderberg Group archives as well as a wide range of private and official collections, it shows the significance of informal diplomacy in a fast-changing world of Cold War, decolonization, and globalization. By analyzing the global mindset of the postwar transatlantic elite and by focusing on private, transnational modes of communication and coordination, this study provides important new insights into the history of transatlantic relations, anti-Americanism, Western anti-communism, and European integration during the 1950s and 1960s. Informal Alliance also debunks the persistent myth that the Bilderberg Group was created by the CIA and repudiates widespread conspiracy theories alleging that Bilderberg was some sort of secret world government.